2020
DOI: 10.1002/smll.201907665
|View full text |Cite
|
Sign up to set email alerts
|

The Nano–Intestine Interaction: Understanding the Location‐Oriented Effects of Engineered Nanomaterials in the Intestine

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/smll.201907665. Engineered nanomaterials (ENMs) are used in food additives, food packages, and therapeutic purposes owing to their useful properties, Therefore, human beings are orally exposed to exogenous nanomaterials frequently, which means the intestine is one of the primary targets of nanomaterials. Consequently, it is of great importance to understand the interaction between nanomaterials and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 146 publications
(162 reference statements)
1
31
1
Order By: Relevance
“…Oral method of administration brings the NPs in immediate contact with the gastrointestinal tract. It is possible that NPs: (i) are accumulated in the mucous layer and either get quickly removed from the organism with the mucous layer renewal, or penetrate the deeper layers of the intestinal wall, remaining in the organism much longer; (ii) display their bactericidal properties by affecting the intestinal microbiota; (iii) interact with the intestinal epithelial cells causing local inflammation, (iv) penetrate the intestinal lymphatic tissue affecting the intestinal immunity; and (v) through the intestinal epithelium reach the bloodstream and affect other organs, the liver in particular [ 74 ]. The mechanisms of further AgNPs action in the organism depend on the type of interaction between the nanoparticles and the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Oral method of administration brings the NPs in immediate contact with the gastrointestinal tract. It is possible that NPs: (i) are accumulated in the mucous layer and either get quickly removed from the organism with the mucous layer renewal, or penetrate the deeper layers of the intestinal wall, remaining in the organism much longer; (ii) display their bactericidal properties by affecting the intestinal microbiota; (iii) interact with the intestinal epithelial cells causing local inflammation, (iv) penetrate the intestinal lymphatic tissue affecting the intestinal immunity; and (v) through the intestinal epithelium reach the bloodstream and affect other organs, the liver in particular [ 74 ]. The mechanisms of further AgNPs action in the organism depend on the type of interaction between the nanoparticles and the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that NPs with a hydrodynamic diameter of smaller than 5.5 nm can rapidly renal clearance [192], and large NPs are absorbed by mononuclear phagocytic system (MPS) of the liver, causing potential hepatotoxicity [193]. The NPs accumulated in the brain may not be excreted for 4 months [194]. The interaction of NPs with brain directly affects CNS homeostasis, or the interaction between NPs and gut microbiota indirectly affects CNS function via the gut-brain axis [194].…”
Section: Conclusion and Prospectivementioning
confidence: 99%
“…The NPs accumulated in the brain may not be excreted for 4 months [194]. The interaction of NPs with brain directly affects CNS homeostasis, or the interaction between NPs and gut microbiota indirectly affects CNS function via the gut-brain axis [194]. Therefore, as an ideal nanomedicine, both long-term and short-term toxicity experiments should be investigated, aiming to achieve maximum therapeutic effects and minimize toxic effects.…”
Section: Conclusion and Prospectivementioning
confidence: 99%
See 1 more Smart Citation
“…Hence, humans are increasingly orally exposed to ENM, which has raised safety concerns [13,14]. In the context of ENM safety evaluation, many authors highlighted the importance to account for the intestinal mucus barrier [15][16][17][18]. On the one hand, the interaction of mucus with ENM, such as the entrapping and the formation of a corona, have been extensively researched both in vitro and in vivo [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%